Adherence of Family Caregivers of Patients with Stroke to Rehabilitation Regimen - Anooshirvan Kazemnejad; Shadan Pedram Razi; Sepideh Mohammadi; Nahid Dehghan Nayeri (Tehran University of Medical Sciences, 2012)
Background & Objective: Due to physical and mental complications, stroke causes disability in self-care and adherence to rehabilitation in patients. The purpose of this study was to assess the adherence to rehabilitation regimen in family caregivers of patients with stroke. Methods & Materials: In this cross-sectional study, 180 family caregivers of patients with stroke were recruited to the study using convenience sampling method. The participants were asked to complete demographic sheet and the Adherence-of-Therapeutic-Regime Questionnaires during two months of stroke. Data were statistically analyzed using descriptive and inferential tests in the SPSS-16. Results: Findings indicated that only about 10% of caregivers were in good levels of adherence to the rehabilitation regimen; and about 25% of them were weak. The weaknesses of the adherence were related to rehabilitation of motion, cognitive and emotional deficiencies, and also prevention of respiratory and skin disorders. Conclusion: According to the study, a small number of family caregivers were in appropriate level for adherence to the rehabilitation regimen. The nurses should be able to empower the family caregivers to decrease physical and psychological disorders related to stroke in patients.